Environmentally Conscious Technologies Using Fungi in a Climate-Changing World - Davor Kržišnik; José Gonçalves (Earth, 2023)
Fungi are a diverse and fascinating group of organisms that play an important role in various ecosystems, e.g., in the decomposition of organic matter and nutrient cycling. However, climate change poses a significant threat to these ecosystems and the organisms that inhabit them. Fluctuations in temperature and humidity can cause shifts in the distribution of fungi and negatively impact the ecosystems they inhabit. Yet fungi have the potential to play a role in mitigating the effects of climate change. With the use of biotechnology, fungi can help meet the United Nations Sustainable Development Goals, and their properties make them useful organisms in addressing the urgent challenges that humanity faces. For example, industrial biotechnology using fungi can lead to the production of goods that are more biodegradable, use less energy and produce less waste. Fungi have long been used in the production of enzymes, alkaloids, detergents, acids, and biosurfactants on an industrial scale. Recent research in the field of white biotechnology has made significant progress, and further advances are expected in the near future, especially in agricultural and environmental biotechnology. With this in mind, it is crucial to explore the use of fungi in novel and environmentally conscious technologies, as well as in mitigating the effects of climate change.